1982
DOI: 10.1111/j.1471-4159.1982.tb04701.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma × Glioma Hybrid Cells Synthesize Enkephalin‐Like Opioid Peptides

Abstract: Partially purified extracts from neuroblastoma X glioma hybrid cells 108CC15 inhibit, like opioids, the prostaglandin E1-evoked formation of cyclic AMP in a dose-dependent manner in the same hybrid cells. The inhibition is prevented by the opioid antagonist naloxone. In addition, the same extract competes with [3H]naloxone and [3H]Leu-enkephalin for binding to opioid receptors of hybrid cell membranes and to a specific antiserum, respectively. The opioid activity in the extracts is destroyed by carboxypeptidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The question remained as to whether these findings could be explained in terms of true ability of some antagonists to reduce the probability of spontaneous interactions between unoccupied receptors and transduction protein, or whether they simply indicated that native membranes were contaminated by an endogenous agonist. Indeed, opioid peptides are synthesized in small amounts by the NG108-15 cell line (25). Fig.…”
Section: Reversibility and Dependence Of The Effect Of Antagonists Onmentioning
confidence: 99%
“…The question remained as to whether these findings could be explained in terms of true ability of some antagonists to reduce the probability of spontaneous interactions between unoccupied receptors and transduction protein, or whether they simply indicated that native membranes were contaminated by an endogenous agonist. Indeed, opioid peptides are synthesized in small amounts by the NG108-15 cell line (25). Fig.…”
Section: Reversibility and Dependence Of The Effect Of Antagonists Onmentioning
confidence: 99%
“…The presence of IR-enkephalins has also been demonstrated at concentrations which can be estimated to be of the same order of magnitude as that found in neuroblastoma x glioma hybrid cells (Glaser et al, 1982). Identity of enkephalins was confirmed by HPLC.…”
Section: Discussionmentioning
confidence: 61%
“…IR-enkephalins have been demonstrated by immunocytochemical methods in dissociated rat spinal cord cultures (Neale et al, 1978), in explant cultures of rat spinal cord (Haynes and Zakarian, 1979), in aggregating cultures from fetal rat brain (Knodel and Richelson, 1980), in dissociated rat brain cell cultures (Weyhenmeyer et al, 1980), and in mouse neuroblastoma (Knodel and Richelson, 1980). Biochemical identification of enkephalins has been performed in neuroblastoma x glioma hybrid cells (Glaser et al, 1982). The presence of IR-somatostatin has been shown in rat hypothalamic cell cultures (Gamse et al, 1980;Peterfreund and Vale, 1982) and in cultures of rat cortical cells (Delfs et al, 1980;Peterfreund and Vale, 1982).…”
Section: Discussionmentioning
confidence: 99%